Long-Term Natural History of Microscopic Colitis: A Population-Based Cohort. Issue 9 (September 2019) - Loreau, Julien; Duricova, Dana; Gower-Rousseau, Corinne; Savoye, Guillaume; Ganry, Olivier; Ben Khadhra, Hajer; Sarter, Hélène; Yzet, Clara; Le Mouel, Jean-Philippe; Kohut, Mathieu; Brazier, Franck; Chatelain, Denis; et al.
Abstract : OBJECTIVES: Data on long-term natural history of microscopic colitis (MC), including collagenous (CC) and lymphocytic colitis (LC), are lacking. METHODS: All new cases of MC diagnosed in the Somme area, France, between January 1, 2005, and December 31, 2007, were prospectively included. Colonic biopsies from all patients were reviewed by a group of 4 gastrointestinal pathologist experts to assess the diagnosis of CC or LC. Demographic and clinical data were retrospectively collected from diagnosis to February 28, 2017. RESULTS: One hundred thirty cases of MC, 87 CC and 43 LC, were included (median age at diagnosis: 70 [interquartile range, 61–77] and 48 [IQR, 40–61] years, respectively). The median follow-up was 9.6 years (7.6; 10.6). By the end of the follow-up, 37 patients (28%) relapsed after a median time of 3.9 years (1.2; 5.0) since diagnosis, without significant difference between CC and LC (30% vs 26%; P = 0.47). Twenty patients (15%) were hospitalized for a disease flare, and 32 patients (25%) presented another autoimmune disease. Budesonide was the most widely used treatment ( n = 74, 59%), followed by 5-aminosalicylic acid ( n = 31, 25%). The median duration of budesonide treatment was 92 days (70; 168), and no adverse event to budesonide was reported. Sixteen patients (22%) developed steroid dependency and 4 (5%) were corticoresistant. No difference in the risk of digestive and extradigestive cancer was observed compared with the general population. None of the death ( n = 25) observed during the follow-up were linked to MC. In multivariate analysis, age at diagnosis (HR, 1.03; 95% confidence interval, 1.00–1.06; P = 0.02) and budesonide exposure (HR, 2.50; 95% confidence interval, 1.11–5.55; P = 0.03) were significantly associated with relapse. DISCUSSION: This population-based study showed that after diagnosis, two-third of the patients with MC observed long-term clinical remission. Age at diagnosis and budesonide exposure were associated with a risk of relapse.